Regulatory non-coding RNAs in crops health and disease - Ferreira, Patrick (2024)
For many years it was thought that the function of RNA was limited to the process of producing proteins. In recent years, scientific discoveries have been proving the multiple roles of different RNAs in different regulatory mechanisms. These RNA’s are collectively called non-coding RNA’s (ncRNA’s). This review presents the latest advances on the different classes of non-coding RNA’s (ncRNA’s) from their function to mechanisms of action. Special emphasis is given to the long non-coding RNAs as new regulatory elements in eukaryote gene expression and in the processes of epigenetic regulation in plants. We believe that increasing studies of regulatory non-coding RNAs in plants will provide a better understanding of the different types of genes related to crop resistance